THE ROLE OF RETINOIDS IN THE TREATMENT OF SKIN AGING: A LITERATURE REVIEW - Ewa Bąkowska; Wojciech Janikowski; Agnieszka Jóźwicka; Aleksandra Stępka; Lena Jaworowicz; Weronika Plichtowicz-Kordowska; Karina Lewandowska; Maria Wieczorek (International Journal of Innovative Technologies in Social Science, 2026)
Skin aging is a progressive biological process involving structural and functional changes such as the thinning of the epidermis, loss of structural integrity, and the development of wrinkles and uneven pigmentation. Retinoids, biologically active compounds derived from vitamin A, represent the most extensively studied pharmacological agents for addressing these age-related alterations. This review synthesized evidence from a comprehensive literature search of PubMed and Google Scholar databases, utilizing Boolean operators and keywords such as "retinoids," "photoaging," and "collagen remodeling" to identify relevant clinical trials, systematic reviews, and histological studies. These agents  exert their effects by modulating gene expression via interaction with nuclear receptors, which leads to increased synthesis of type I and III procollagen and the inhibition of matrix metalloproteinases. Tretinoin continues to be the gold standard in therapy, offering the strongest clinical and histological evidence for improving photodamaged skin, although its use is often limited by dose-dependent irritation. Derivatives such as retinol and retinaldehyde provide significant clinical benefits with improved tolerability, making them suitable for long-term maintenance and individuals with sensitive skin. Furthermore, tazarotene shows robust efficacy for photodamage comparable to tretinoin, while isotretinoin remains a potent off-label option restricted by its systemic safety profile. Clinical selection of retinoids should be individualized, balancing efficacy with patient adherence, while future research should focus on advanced delivery systems and the separate evaluation of intrinsic and extrinsic aging pathways.